Analisis studi kelayakan bisnis kerupuk amplang ikan tenggiri: Studi kasus pada UD RAR Crackers - HN, Lailatus Syarifah; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
A feasibility study is an evaluation that becomes the basis for decision making related to the acceptance or rejection of a planned business idea. This study uses descriptive research by reviewing and analyzing the business of mackerel amplang crackers on UD RAR Crackers using primary and secondary data. The results showed that the business feasibility study on UD RAR Crackers on environmental, management and human resources, as well as technical and technological aspects was feasible but for legal aspects as well as market and marketing was still quite feasible. In running a business, it is important to pay attention to licensing to prevent future risks. In addition, to achieve maximum profits and reduce the threat of competitors, it is necessary to focus on marketing strategies, especially in promotion and distribution, in order to increase efficiency compared to similar products. This aims to minimize the risk of threats from outside parties to the product being run.